Investigation into the operation of a cement works precalciner vessel - Giddings, Donald (2000)
This Ph.D thesis describes an investigation into the operation of the Blue Circle Cauldon Works precalciner vessel. The vessel is part of the cement making plant and it serves the purpose of providing a furnace that is maintained at approximately 900C to calcine the limestone in the raw meal prior to cementation in the kiln. At Cauldon, tyre chips are used as a support fuel. It was the aim of this work to predict the likely behaviour of the gases and particles in the precalciner by using Computational Fluid Dynamics modelling. The commercial code Fluent was used. Investigation of the likely trajectories and combustion behaviour of tyre chips was particularly important. In this way it was hoped that a method of assessing the suitability of alternative waste fuels for incineration in the precalciner might be established.